The Essence Of Elementary School Teacher Performance: Exploring The Role Of Self-Efficacy And Teacher Competence - Bianca Ayu Prastika (International Islamic Schools Alliance, 2025)
This study aimed to determine and test data related to the correlation between self- efficacy and professional competence of teachers with teacher performance in elementary schools. The sample of this study is 61 teachers at SD Negeri Sindet, SD Muhammadiyah Blawong I, SD Muhammadiyah Blawong II. The data collection technique in this study is a questionnaire. The data collection instruments in this study used teacher performance questionnaires, self-efficacy scales, and professional competency scales. The data analysis techniques in this study were carried out quantitatively using descriptive statistical methods, the Kolmogorov- Smirnov One- Sample normality test, the product-moment correlation test from Pearson, and multiple linear regression analysis assisted by SPSS 25.0 software. Based on the results of data analysis, it is known that teachers' self-efficacy and professional competence have an effect on teacher performance simultaneously.